SERVQUAL METHOD ANALYSIS FOR GENERAL PATIENT HEALTH SERVICE SATISFACTION LEVEL - Dyna Monica Dyna Monica; Irianto; Adi Mas Afandi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Puskesmas Pulo Bandring is a functional implementing unit that functions as a center for health development. as a center for health services for the community, Puskesmas are required to always maintain patient trust, by improving the quality of their services. However, in reality in the field there is no system that can measure the level of satisfaction of health services at the Puskesmas Pulo Bandring. To overcome this problem, the researcher uses the Servqual Method, Service Quality is a method used to measure the service quality of the attributes of each dimension, so that the gap value will be obtained which is the difference between consumer perceptions of the services that have been received and expectations of what will be received. received. The data that was processed in this study was obtained by giving a chair containing 22 questions to 30 patients seeking treatment at the Puskesmas Pulo Bandring. It was found that the satisfaction of patients seeking treatment at Puskesmas Pulo Bandring Public seen from the 5 dimensions of the servqual had a reality value of 4.00 and an expected value of 4.62 so that there was a gap of -0.62. This gap occurs due to the non-fulfillment of patient expectations with the quality of services provided by the Puskesmas Pulo Bandring. . Keywords: health services, servqual method, patients, puskesmas